2012
DOI: 10.1111/j.1471-4159.2012.07646.x
|View full text |Cite
|
Sign up to set email alerts
|

Serine hydroxymethyltransferase 1 and 2: gene sequence variation and functional genomic characterization

Abstract: Serine hydroxymethyltransferase (SHMT) catalyzes the transfer of a beta carbon from serine to tetrahydrofolate (THF) to form glycine and 5,10-methylene-THF. This reaction plays an important role in neurotransmitter synthesis and metabolism. We set out to resequence SHMT1 and SHMT2, followed by functional genomic studies. We identified 87 and 60 polymorphisms in SHMT1 and SHMT2, respectively. We observed no significant functional effect of the 13 nonsynonymous SNPs in these genes, either on catalytic activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…SHMT enzymes catalyze the conversion of serine to glycine by catalyzing the transfer of the b-carbon of serine to tetrahydrofolate (THF) generating 5,10-methylene-THF and glycine (30,31). Phosphoglycerate dehydrogenase (PHGDH), another enzyme in the pathway of generating glycine from glucose, was recently shown to be amplified in melanoma (32) and breast cancer (33) and the next enzyme in this pathway, phosphoserine aminotransferase, is overexpressed in colorectal cancers, associated with chemoresistance (34), and required for serine pathway flux in breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…SHMT enzymes catalyze the conversion of serine to glycine by catalyzing the transfer of the b-carbon of serine to tetrahydrofolate (THF) generating 5,10-methylene-THF and glycine (30,31). Phosphoglycerate dehydrogenase (PHGDH), another enzyme in the pathway of generating glycine from glucose, was recently shown to be amplified in melanoma (32) and breast cancer (33) and the next enzyme in this pathway, phosphoserine aminotransferase, is overexpressed in colorectal cancers, associated with chemoresistance (34), and required for serine pathway flux in breast cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…Among the six proteins included in that analysis, GNMT, MAT1A, and BHMT are expressed predominantly in adult human liver, whereas COMT and SHMT1 are ubiquitously expressed. In a previous analysis of methionine and folate cycle mRNA expression in the Human Variation Panel lymphoblastoid cell lines that were used as a source of DNA for our gene resequencing studies (Hebbring et al, 2012), we observed strong correlations among mRNA expression levels for SHMT1, SHMT2, COMT, MAT2A, and MAT2B (Hebbring et al, 2012). Unfortunately, MAT1A, GNMT, and BHMT are not expressed in lymphoblastoid FIG.…”
Section: Discussionmentioning
confidence: 78%
“…This study indicated that low AGL expressing cells rely upon glucose to help drive increased glycine synthesis (9). This evidence was supported by the amplified serine hydroxymethyltransferase 2 (SHMT2) gene, responsible for glycine synthesis (13,14). In addition, elevated expression of SHMT2 correlates with poor patient prognosis in bladder cancer patients with low AGL expression, verifying the importance of glycine synthesis in AGL low bladder cancer (9).…”
Section: Agl Glycogen Metabolism and Regulation Of Glycine Synthesismentioning
confidence: 74%